Nursing ethics through the life span - Bandman, Elsie L. (Appleton & Lange, 1990)
This two-part book begins with a discussion of the moral foundations and significance of nurse-client-physician relationships. Models of morality are developed along with values and priorities as guidelines for decision making. These ethics are applied in the second part, beginning with the procreative family and progressing through the life span. Some of the moral-philosophical nursing problems addressed in Part Two include abortion, infancy, the aging, and the dying.